The Paris detective - Patterson, James, 1947-; DiLallo, Richard (Patterson, James, 1947- Detective Luc Moncrief story ;, 2021)
A new bind-up with three exciting thrillers featuring NYPD Detective Luc Moncrief, a Paris detective who's about to learn that NYC is a whole other ballgame in the world of crime. French Twist: Gorgeous women are dropping dead at upscale department stores in New York City. Detective Luc Moncrief and Detective Katherine Burke are close to solving the mystery, but looks can be deceiving. French Kiss: Very handsome and charming French detective Luc Moncrief joined the NYPD for a fresh start, but someone wants to make his first big case his last. Welcome to New York. The Christmas Mystery: In the heart of the holiday season, priceless paintings have vanished from a Park Avenue murder scene. Now, dashing French detective Luc Moncrief must become a quick study in the art of the steal, before a coldblooded killer paints the town red. Merry Christmas, Detective.